LITERASI MEDIA DIGITAL DALAM KELUARGA DI MASA PANDEMI CORONA VIRUS DISEASE 2019 - Luh Suryatni (Fakultas Ilmu Komputer dan Desain - Unsurya, 2022)
Restrictions on activities by government policies bring the public to get to know more about the use of digital media that have the capacity and internet network. Once the policy takes effect a clear change occurs to the number of users of social media, online applications and various internet-based platforms. Starting from the place of business, workplace to centralized education institution with the use of internet-based digital media to connect every citizen who lives in their respective homes to keep their obligations. The purpose of this paper is to find out and analyzing the importance of digital media literacy in families during the Corona Virus Disease 2019 (COVID-19) pandemic. The data collection method used is a literature study with descriptive analysis techniques. The results are showed that digital media literacy in the family is very important in the COVID-19 pandemic so that families can prevent negative influences of bad content harming their family members.Â Key words: digital media literacy, family and COVID-19 pandemic.Â